Silvanus Phillips Thompson e a desmistificação do cálculo: resgatando uma história esquecida - Miranda, Gustavo Alexandre de (2004)
With the purpose of studying the calculus teaching history and, particularly, the consequences of Calculus Made Easy (1910) in the mathematics education context, this work intends to make an historical analysis to clarify the connections between Silvanus Phillips Thompson (its author) and the education in the early twentieth century, mainly mathematics education. Thompson was concerned about Physics and Radiology, however, at the dawn of the new century, his interests in technical education had also burgeoned. One of his goals was to demystify Calculus, tackling the subject intuitively Calculus Made Easy. The book did not draw much respect from mathematicians and was acridly criticized